Distinct neuroprotective and anti-inflammatory effects of Kampo formulas ninjinyoeito and juzentaihoto in depression-like SAMP8 mice - Maruko, Akiko; Ito, Naoki; Oshima, Kenshiro; Nishi, Akinori; Kobayashi, Yoshinori; Okada, Norihiro (Frontiers in Pharmacology, 2025)
IntroductionIn contemporary aging societies, preventing and ameliorating mental and physical frailty is essential. Kampo formulas, including ninjinyoeito (NYT) and juzentaihoto (JTT), have been used traditionally to treat frailty in the elderly. NYT has been reported to alleviate psychological frailty such as depression and anxiety. This study aimed to clarify the mechanisms underlying the effects of these two Kampo formulas in the early stages of neurodegeneration associated with psychiatric disorders.MethodsGenes affected by Kampo formulas were comprehensively investigated by administering JTT or NYT to senescence accelerated mouse prone 8 (SAMP8) mice, from 7 weeks, and by RNA sequencing of the hippocampus at 19 weeks when depression and anxiety behaviors typically emerge. Additionally, we examined the impact of these Kampo formulas on neuroinflammation induced by lipopolysaccharide (LPS).ResultsThe two Kampo formulas alleviated the depressive-like behavior of SAMP8 mice, as demonstrated by the restoration of microglial cell activation, DNA repair, stress-responsive transcription factor expression, and nervous system development-related gene expression. However, the NYT-administrated group presented a greater number of recovered genes than did the JTT-administrated group, and NYT additionally suggests that the potential inhibition of age-related mitochondrial dysfunction and increased oxidative stress. The administration of LPS resulted in elevated expression levels of immune and inflammation-related genes and increased astrocyte activity in SAMP8 mice. JTT mitigated these effects by suppressing the expression of the LPS receptor TLR4 and its downstream target NF-κB. In contrast to JTT, NYT maintained and increased the expression of genes associated with neuroprotective functions in microglia.DiscussionThe two Kampo formulas exerted neuroprotective effects by enhancing neural and glial stress responses in the early stages of neurodegeneration. Under condition of acute inflammation, JTT and NYT alleviated neuronal damage via the suppression of microglial activity and the enhancement of microglial neuroprotection, respectively. These findings provide novel insights into the mechanism of action of NYT, which has been reported to ameliorate psychological frailty associated with aging, and further suggest that JTT may exert effects against inflammatory neurodegeneration.